Chapter The cost-effectiveness of what in health and care? - Mitchell, Paul Mark (Kohlhammer Verlag, 2021)
Assessing the value for money offered by new health technologies is playing an increasingly important role in aiding decision-making in health and care. Even in a pre-COVID-19 world, international healthcare systems were struggling to meet the demands of their patient populations and the rising cost of new health technologies, such as pharmaceuticals. With the impact of the corona virus pandemic on the global economy and the provision of other health and care services more generally, difficult decisions will continue to be required over what basket of health and care services are available to the general popu lation. Health economists have developed methods to aid decision-makers who want to improve population health as the primary goal. Tools such as quality adjusted life years (QALYs) combine health-related quality of life and quantity of life into a single outcome. QALYs allow for population health to be maxim ised. However, there is debate over whether the quality of life content cap tured by QALYs is too narrow. In addition, the aim of maximisation in health may be at odds with other goals of health and care, such as reducing health inequalities. This chapter discusses some of the key steps involved in the construction of the QALY to value patient benefits from health and care interventions, and also how the QALY is commonly used in economic evaluation to aid healthcare decision-making. A critique and an alternative to QALYs is also provided. Evaluating peoples capabilities has been proposed as an alternative to health focused outcomes, such as QALYs, to inform health and care decision making. Developed initially by nobel prize winning economist and philosopher, Amartya Sen, capabilities represent what a person is able to do and be in life that they have reason to value. Although health functionings are an important component of Sen's Capability Approach, using QALYs does not fully extend the evaluative focus on to how such health outcomes and other non-health functionings are reflective of what people can and cannot do in their life that they have reason to value. Aiming to get people to a decent or sufficient level of capability also provides an alternative to the health maximisation objective commonly pursued in health economic evaluations. Adopting a different quality of life measurement approach in health eco nomic evaluations, as well as a new objective, has important implications for what patients and treatments are prioritised in health and care. Previous re search has shown how interventions that improve quality of life for patients with mental health conditions and more severe health conditions will be more favourably treated using a capability measure. It is also recognised that health inequality has largely been neglected in the singular focus of QALY maximisa tion. Shifting to a "sufficient capability" objective may help address efficiency and equity concerns without the need for more complex economic evaluation frameworks that require dual objectives to deal with population health and health inequality simultaneously.